Influence of Melatonin on the Proliferative and Apoptotic Responses of the Prostate under Normal and Hyperglycemic Conditions - Marina G. Gobbo; Nishtman Dizeyi; Per-Anders Abrahamsson; Per-Anders Bertilsson; Viviane Sanches Masitéli; Eloisa Zanin Pytlowanciv; Sebastião R. Taboga; Rejane M. Góes (Journal of Diabetes Research)
The antitumor properties of melatonin (MLT) are known for prostate cancer cells. This study investigated whether MLT affects prostate maturation and interferes with tissue injuries induced by diabetes. MLT was administered to Wistar rats from 5 weeks of age in the drinking water (10 μg/kg b.w.), and diabetes was induced at the 13th week by streptozotocin (4.5 mg/100g b.w., i.p.). The animals were euthanized in the 14th and 21st weeks. MLT reduced the immunostained cells for androgen receptor (AR) by 10% in younger rats. Diabetes decreased cell proliferation and increased apoptosis. MLT treatment impeded apoptosis p=0.02 and augmented proliferation p=0.0008 and PCNA content in prostate following long-term diabetes due to restoration of testosterone levels and expression of melatonin receptor type 1B. The effect of MLT (500 µM, 5 mM, and 10 mM) on androgen-dependent (22Rv1) and androgen-independent (PC3) cancer cells and human prostate epithelial cells (PNTA1) under normal and hyperglycemic conditions (HG, 450 mg/dL) was analyzed. Contrary to PNTA1 and 22Rv1 cells, MLT improved the proliferation of PC3 cells in hyperglycemic medium. The combined data indicated that MLT had proliferative and antiapoptotic effects in prostate cells subjected to HG levels and it seems to involve specific MLT pathways rather than AR.